The Role of Hypoxia-inducible Factor in Mycobacterium tuberculosis-infected Macrophages - Fitriana, Nina; Iswanti, Febriana Catur; Sadikin, Mohamad (Cell and BioPharmaceutical Institute, 2024)
Tuberculosis is caused by Mycobacterium tuberculosis infection. During M. tuberculosis infection, there is a decrease in the partial pressure of oxygen in the granuloma microenvironment, which causes the hypoxia-inducible factor (HIF) to become stable. HIF functions as a transcription factor that regulates the expression of genes crucial for metabolic adaptation in hypoxic conditions. Recent research suggests that HIF plays a vital role in infectious and inflammatory conditions. Several studies have demonstrated that HIF signaling can enhance macrophages antimicrobial activity and bactericidal effect against M. tuberculosis, such as increasing macrophage autophagy, enhancing the effects of rifampicin, inhibiting p38 MAPK signaling, enhancing the regulation of effector antimicrobial pathways mediated by human β defensin 2 (hBD2) and vitamin D receptor (VDR), redirecting energy metabolism to glycolysis, and producing various cytokines. All these responses ultimately result in the inhibition of intracellular M. tuberculosis growth. HIF has therapeutic implications, potentially being a new candidate for host-directed therapy as a complement to existing antituberculosis drugs. Understanding the role of HIF in macrophages during M. tuberculosis infection and comprehending the host-pathogen relationship with M. tuberculosis is advantageous for developing future therapies.Keywords: Mycobacterium tuberculosis, macrophages, hypoxia-inducible factor